Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the logarithmic equation
[tex]\[ \log_2(x + 2) = 1 + \log_2(x - 5), \][/tex]
follow these steps:
### Step 1: Understand the Equation
First, recognize that the logarithms are both to the base 2.
[tex]\[ \log_2(x + 2) \][/tex]
[tex]\[ \log_2(x - 5) + 1 \][/tex]
### Step 2: Isolate the Logarithmic Terms
To simplify the equation, subtract \(\log_2(x - 5)\) from both sides:
[tex]\[ \log_2(x + 2) - \log_2(x - 5) = 1 \][/tex]
### Step 3: Apply Logarithmic Properties
Use the property of logarithms that states \(\log_b(a) - \log_b(c) = \log_b\left( \frac{a}{c} \right)\):
[tex]\[ \log_2 \left(\frac{x + 2}{x - 5}\right) = 1 \][/tex]
### Step 4: Eliminate the Logarithm
Remember, if \(\log_b(A) = C\), then \(A = b^C\). In this case, \(b = 2\) and \(C = 1\):
[tex]\[ \frac{x + 2}{x - 5} = 2^1 \][/tex]
[tex]\[ \frac{x + 2}{x - 5} = 2 \][/tex]
### Step 5: Solve the Resulting Equation
Multiply both sides by \(x - 5\) to cancel the denominator:
[tex]\[ x + 2 = 2(x - 5) \][/tex]
[tex]\[ x + 2 = 2x - 10 \][/tex]
Rearrange to isolate \(x\):
[tex]\[ 2 + 10 = 2x - x \][/tex]
[tex]\[ 12 = x \][/tex]
### Step 6: Verify the Solution
Ensure that the solution makes the original logarithmic arguments valid:
- \( x + 2 \) must be greater than 0: \( 12 + 2 > 0 \) which simplifies to \( 14 > 0 \) (true).
- \( x - 5 \) must be greater than 0: \( 12 - 5 > 0 \) which simplifies to \( 7 > 0 \) (true).
Since both conditions are satisfied, the solution \( x = 12 \) is valid.
### Conclusion
The solution to the equation \(\log_2(x + 2) = 1 + \log_2(x - 5)\) is
[tex]\[ x = 12 \][/tex]
[tex]\[ \log_2(x + 2) = 1 + \log_2(x - 5), \][/tex]
follow these steps:
### Step 1: Understand the Equation
First, recognize that the logarithms are both to the base 2.
[tex]\[ \log_2(x + 2) \][/tex]
[tex]\[ \log_2(x - 5) + 1 \][/tex]
### Step 2: Isolate the Logarithmic Terms
To simplify the equation, subtract \(\log_2(x - 5)\) from both sides:
[tex]\[ \log_2(x + 2) - \log_2(x - 5) = 1 \][/tex]
### Step 3: Apply Logarithmic Properties
Use the property of logarithms that states \(\log_b(a) - \log_b(c) = \log_b\left( \frac{a}{c} \right)\):
[tex]\[ \log_2 \left(\frac{x + 2}{x - 5}\right) = 1 \][/tex]
### Step 4: Eliminate the Logarithm
Remember, if \(\log_b(A) = C\), then \(A = b^C\). In this case, \(b = 2\) and \(C = 1\):
[tex]\[ \frac{x + 2}{x - 5} = 2^1 \][/tex]
[tex]\[ \frac{x + 2}{x - 5} = 2 \][/tex]
### Step 5: Solve the Resulting Equation
Multiply both sides by \(x - 5\) to cancel the denominator:
[tex]\[ x + 2 = 2(x - 5) \][/tex]
[tex]\[ x + 2 = 2x - 10 \][/tex]
Rearrange to isolate \(x\):
[tex]\[ 2 + 10 = 2x - x \][/tex]
[tex]\[ 12 = x \][/tex]
### Step 6: Verify the Solution
Ensure that the solution makes the original logarithmic arguments valid:
- \( x + 2 \) must be greater than 0: \( 12 + 2 > 0 \) which simplifies to \( 14 > 0 \) (true).
- \( x - 5 \) must be greater than 0: \( 12 - 5 > 0 \) which simplifies to \( 7 > 0 \) (true).
Since both conditions are satisfied, the solution \( x = 12 \) is valid.
### Conclusion
The solution to the equation \(\log_2(x + 2) = 1 + \log_2(x - 5)\) is
[tex]\[ x = 12 \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.